Typological differentiation and influence mechanisms of gender role attitudes among Chinese women - Chi, Ruihua; Zhou, Jin (Frontiers in Psychology, 2025)
With the current accelerated evolution of globalization, developing countries, represented by China, are experiencing a reshaping of gender concepts due to the impact of multiculturalism. Based on data from the China General Social Survey 2010–2021, this study uses latent profile analysis to identify different types of Chinese women’s gender role attitudes. In addition, this study comprehensively analyzes the influencing mechanisms of the differentiation of gender role attitudes types, and longitudinally compares the evolutionary trends of Chinese women’s gender role attitudes types. The conclusions of the study are as follows. First, Chinese women’s gender role attitudes are diversified, and there are four types: multidimensional traditional, social division of labor traditional, innate ability traditional and completely modern. Secondly, according to the different influencing mechanisms, this paper classifies the factors affecting the differentiation of Chinese women’s gender role attitudes into three categories: external environment-driven, intrinsic interest-driven, and comprehensive-driven. Finally, since 2010, the pattern of Chinese women’s gender role attitudes has evolved from being dominated by the “multidimensional traditional type” to the “fully modern type.” However, through precise characterization, it is found that the evolutionary trends of women holding the four types of gender role attitudes are different.